Optimization of ion transport in a combined RFQ Cooler with axial magnetic field. Issue 1 (1st April 2022) - Cavenago, M.; Romé, M.; Maero, G.; Bellan, L.; Cavaliere, F.; Comunian, M.; Galatà, A.; Maggiore, M.; Panzeri, N.; Pisent, A.; Pranovi, L.; Sattin, M.
Abstract: The accurate mass spectrometry (with resolution goal 1:20000) of exotic ions requests beams with low energy spread (goal is about 0.5 eVrms or lower) and low transverse emittance, so it is necessary to cool ions produced by a fission source. In a radiofrequency (rf) quadrupole cooler (RFQC), collisions decrease ion kinetic energy, while rf and DC voltages confine and reaccelerate ions towards the extraction, where the cold ion beam is formed. Operation is based on carefully chosen tunings of voltages and of gas pressure p g, which requires an adequate pumping system; efficient simulations of extraction systems, which critically depend on residual speed of ions, are also important. Progresses in the experimental setup are described. Indications from simple ray tracing and 'ray+collision' tracing are compared. Results are applied to a simple triode extraction system, and more flexible configurations are considered.